Mental health, institutional psychology and socialhistorical-polity perspective: A propose of psychology training: The case of La Plata city 1966-1969 - D'agostino, Agustina María Edna (2016)
This article presents the training proposal by Psychology students of the Faculty of Psychology at the National University of La Plata (1969). Techniques used include interviews and document analysis. We make the following conclusions: Students were interested in a historical and political social project, and wanted to include group, institutional and community practices in training. Was present the commitment to transform society. Mental health was conceived as a result of socio-economic context. A critique of the hegemonic medical models is observed, psychiatric care of mental illness.